2013
DOI: 10.1093/cercor/bht290
|View full text |Cite
|
Sign up to set email alerts
|

Cdk5 Phosphorylation of ErbB4 is Required for Tangential Migration of Cortical Interneurons

Abstract: Interneuron dysfunction in humans is often associated with neurological and psychiatric disorders, such as epilepsy, schizophrenia, and autism. Some of these disorders are believed to emerge during brain formation, at the time of interneuron specification, migration, and synapse formation. Here, using a mouse model and a host of histological and molecular biological techniques, we report that the signaling molecule cyclin-dependent kinase 5 (Cdk5), and its activator p35, control the tangential migration of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 51 publications
0
27
0
Order By: Relevance
“…For example, Rakic and colleagues beautifully demonstrated that MGE-cells are able to migrate towards three ErbB4 ligands, which are extensively expressed in vivo by non-interneurons of the developing forebrain [28]. …”
Section: How To Study Neuronal Migration In the Cerebral Cortexmentioning
confidence: 99%
“…For example, Rakic and colleagues beautifully demonstrated that MGE-cells are able to migrate towards three ErbB4 ligands, which are extensively expressed in vivo by non-interneurons of the developing forebrain [28]. …”
Section: How To Study Neuronal Migration In the Cerebral Cortexmentioning
confidence: 99%
“…A recent study further revealed that Cdk5-mediated phosphorylation of receptor tyrosine-protein kinase erbB-4 (ErbB4) at Tyr1056, a docking site for PI3-kinase, is necessary for tangential migration of interneurons both toward and within the cerebral cortex [66] (Table 1). Importantly, phosphorylated ErbB4 reside in close proximity to MTs in adult interneurons, suggesting that Cdk5-directed migration of cortical interneurons likely occurs through MT cytoskeletal remodeling.…”
Section: Role Of Cdk5 In Neuronal Migrationmentioning
confidence: 99%
“…The cortical migration of GABAergic interneurons (Guo and Anton, ) occurs at a different mode and is regulated by different mechanisms of microtubule modulation (Eom et al, ). However, these do share some fundamental features with projection neurons, such as the requirement for N‐cadherin (Luccardini et al, ) and CDK5 activity (Rakić et al, , ). An interesting emerging realization pertaining to cortical interneuron migration is the role of signaling from the primary cilium (Baudoin et al, ; Métin and Pedraza, ).…”
Section: Roles Of Other Members Of the Small Gtpase Family In Neuron mentioning
confidence: 99%